2005
DOI: 10.1210/en.2004-0665
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Caloric Food Restriction Affects Insulin-Like Growth Factor System in Fetal Wistar Rat

Abstract: We have previously shown that fetuses from protein-caloric undernourished pregnant rats (35% of control diet during the last week of pregnancy) at 21.5 d post coitum exhibit increased beta-cell mass. This alteration is correlated with increased insulinemia and total pancreatic insulin content, a pattern similar to that reported in infants of mild diabetic mothers. In this work, we investigated in undernourished fetuses: 1) whether availability of growth factors such as insulin, GH, and IGFs and their binding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
4
24
0
Order By: Relevance
“…IGFs are highly responsive to nutritional status (51), and IGF-I, which is expressed in adult pancreas (12), is independent of GH (33,39). Most studies on nutritional regulation of IGF-I have shown that undernutrition decreased circulating IGF-I and/or hepatic IGF-I mRNA expression and protein abundance in the neonatal and adult periods (17,40,44,54) as well as in the fetal period (14,38,50). The decreased serum IGF-I levels observed in U adult rats before Px (Table 1), probably due to decreased liver IGF-I mRNA expression, are in accord with the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…IGFs are highly responsive to nutritional status (51), and IGF-I, which is expressed in adult pancreas (12), is independent of GH (33,39). Most studies on nutritional regulation of IGF-I have shown that undernutrition decreased circulating IGF-I and/or hepatic IGF-I mRNA expression and protein abundance in the neonatal and adult periods (17,40,44,54) as well as in the fetal period (14,38,50). The decreased serum IGF-I levels observed in U adult rats before Px (Table 1), probably due to decreased liver IGF-I mRNA expression, are in accord with the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 80%
“…Specific receptors for IGF-I have been described in rat pancreatic ␣-and ␤-cells and murine acinar tissue (52), and IGF-I has been localized to islet ␤-cells by immunohistochemistry (26). The IGF axis is highly responsive to nutritional status (51), and experimentally induced growth retardation in the rat has been associated with a reduction in circulating IGF levels and altered presence of IGFBPs (38,50). Furthermore, it has been described that IGF-I is expressed in areas of regeneration after partial pancreatectomy (20), suggesting that IGF-I may play a main role in the growth and differentiation of normal pancreatic tissues.…”
mentioning
confidence: 99%
“…The pancreas is a plastic organ, and early life events may play a role in determining the capacity for adult pancreatic plasticity. Several animal models have demonstrated altered pancreatic development following in utero deprivation [67][68][69][70]. A group of imprinted genes including Igf2, Rasgrf, Grb10, Neuronatin and Zac1 play key roles in pancreatic development and maturation and may be involved in the pathogenesis of these defects, although direct evidence of this remains scanty.…”
Section: Imprinted Genes and The Pancreatic Consequences Of In Utero mentioning
confidence: 99%
“…Evidence for the involvement of the IGF family in beta cell development is abundant and based on physiological studies [7] and genetic mouse models [7][8][9] as follows: (1) IGFs are mitogenic for beta cells [7]; (2) IGFs and their binding proteins are produced in fetal and adult pancreata [10]; (3) IGFs act as cell survival factors by inhibiting beta cell apoptosis [7]; (4) IGF2 overexpression in transgenic mice causes islet hyperplasia [11]; and (5) undernourished fetuses with an increased beta cell mass have locally increased pancreatic Igf1 expression [12].…”
mentioning
confidence: 99%